Compact tri‐band BPF applying novel multi‐mode microstrip resonator. Issue 6 (28th April 2016) - Chen, Jianzhong; Wu, Zixian; Shi, Hongyu; Lin, Lei
ABSTRACT: This article presents a novel multi‐mode microstrip resonator. Using the even‐odd‐mode method, its resonance characteristics are analyzed and the design graphs are given. Each mode equivalent circuit is a λ /4 stepped impedance resonator (SIR), so the proposed resonator has a compact size and the higher harmonics can be tuned in a wide range. Stub–stub coupling is introduced to split two identical modes and produce two transmission zeros (TZs). Then a tri‐band filter operating at 1.5, 2.4, and 3.8 GHz is designed using the proposed resonator. The three center frequencies and bandwidths can be independently controlled. By tuning the impedance and length ratios of the stubs, wide upper stopband is achieved. Finally, the designed filter is fabricated and measured, and the measured results agree well with the simulated ones. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:559–564, 2016.